Pengaruh Penggunaan Media Papan Nilai Tempat Terhadap Kemampuan Mengenal Nilai Tempat Pada Kelas III di SD Negeri 25 Kota Banda Aceh - Miftah Hulzanah; Ahmad Nasriadi; Tria Marvida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of using place value boards on the ability of third-grade students to recognize place value at SD Negeri 25, Banda Aceh City. Place value is a basic concept in mathematics that is very important as a foundation for understanding arithmetic operations.However, many students still experience difficulties because learning is often delivered abstractly and lacks concrete media support. This study used a quantitative approach with a one-group pretest–posttest design. The subjects were third-grade students who were first given a pretest, then received treatment through learning using a place value board, and finally, a posttest. The instruments used included tests, observation sheets, and documentation. The analysis results showed a significant improvement in student learning outcomes after the implementation of the place value board. Furthermore, student activity and engagement in the learning process also increased. Students found it easier to understand the position and value of a number and were more enthusiastic in participating in learning activities. Thus, it can be concluded that the use of the place value board has a positive influence on the ability to recognize place value in grade III students. This media can be used as an alternative learning medium for mathematics in elementary schools to make learning more concrete, interesting, and meaningful